Insegurança alimentar, gênero e raça/cor: um estudo no semiárido nordestino - Pereira, Thaís da Conceição (2024)
Among the social determinants of food insecurity (FI), gender and race/color inequality are revealed in food security issues as vulnerability factors that determine and enhance the severity levels of FI. This study analyzed the association between AI, gender, and race/color of reference people in households in a municipality in the northeastern semi-arid region. This is a cross sectional study carried out through household interviews (n=737) using a semi-structured questionnaire and the Brazilian Food Insecurity Scale (EBIA) with families living in urban and rural areas of the municipality of Cuité-PB. Self-declared gender and race/color profiles were created (white man, white woman, black man, and black woman) and analyzed with food safety and AI levels (mild and moderate/severe). Multinomial logistic regression models were applied to estimate the association between profiles and AI levels adjusted based on socioeconomic and demographic conditions (age, marital status, education, occupation, number of residents, child/adolescent in the household, per capita income family, access to Bolsa Família, living area and type of household). It was found that the risk of being in moderate/severe FI was 5.1 times higher (95% CI: 1.8–14.8) in households where a black woman was the reference person, 4.8 (95% CI: 1.4–16.0) and 4 (95%CI:1.2–13.7), among white women and black men, respectively, when compared to white men. Monthly family per capita income <=¼ MW and low education were significantly associated with the outcome of moderate/severe FI. Therefore, these determinants must be included in formulating and implementing public policies, strategies, and actions related to AI, as well as favoring and guaranteeing social justice and the right to adequate food.